Genome architecture used to supplement species delineation in two cryptic marine ciliates. (26th June 2022) - Smith, Susan A.; Santoferrara, Luciana F.; Katz, Laura A.; McManus, George B.
Abstract: The purpose of this study is to determine which taxonomic methods can elucidate clear and quantifiable differences between two cryptic ciliate species, and to test the utility of genome architecture as a new diagnostic character in the discrimination of otherwise indistinguishable taxa. Two cryptic tintinnid ciliates, Schmidingerella arcuata and Schmidingerella meunieri, are compared via traditional taxonomic characters including lorica morphometrics, ribosomal RNA (rRNA) gene barcodes and ecophysiological traits. In addition, single‐cell 'omics analyses (single‐cell transcriptomics and genomics) are used to elucidate and compare patterns of micronuclear genome architecture between the congeners. The results include a highly similar lorica that is larger in S. meunieri, a 0%–0.5% difference in rRNA gene barcodes, two different and nine indistinguishable growth responses among 11 prey treatments, and distinct patterns of micronuclear genomic architecture for genes detected in both ciliates. Together, these results indicate that while minor differences exist between S. arcuata and S. meunieri in common indices of taxonomic identification (i.e., lorica morphology, DNA barcode sequences and ecophysiology), differences exist in their genomic architecture, which suggests potential genetic incompatibility. Different patterns of micronuclear architecture in genes shared by both isolates also enable the design of species‐specific primers, which are used in this study as unique "architectural barcodes" to demonstrate the co‐occurrence of both ciliates in samples collected from a NW Atlantic estuary. These results support the utility of genomic architecture as a tool in species delineation, especially in ciliates that are cryptic or otherwise difficult to differentiate using traditional methods of identification.